2011
DOI: 10.1007/s11274-011-0899-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a loop-mediated isothermal amplification assay for detection of Cronobacter spp. (Enterobacter sakazakii)

Abstract: Contamination of Cronobacter spp. (Enterobacter sakazakii) in infant formulas and other food products is a severe problem. Here a loop-mediated isothermal amplification (LAMP) assay was developed for rapidly detecting Cronobacter spp. in powdered infant formula. Sequences of 16S/23S rDNA internal intergenic spacer of Cronobacter spp. were used as the target template to design LAMP primers. The detection outcome can be evaluated by the white precipitate or the fluorescence intensity under ultraviolet irradiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 12 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…A number of alternative molecular methods for Cronobacter spp. have been investigated, including conventional PCR assay using 16S rRNA [6], OmpA or rpoB genes [15], [16], real time PCR using TaqMan and SYBR Green [3], [9], and the loop-mediated isothermal amplification [17]. However, real-time PCR requires expensive labelled probe, and LAMP may have high risk of amplicon contamination.…”
Section: Introductionmentioning
confidence: 99%
“…A number of alternative molecular methods for Cronobacter spp. have been investigated, including conventional PCR assay using 16S rRNA [6], OmpA or rpoB genes [15], [16], real time PCR using TaqMan and SYBR Green [3], [9], and the loop-mediated isothermal amplification [17]. However, real-time PCR requires expensive labelled probe, and LAMP may have high risk of amplicon contamination.…”
Section: Introductionmentioning
confidence: 99%
“…By using sequences of 16S‐23S rDNA ITS region as a template to design primers, numerous other studies have reported the superior sensitivity of LAMP in comparison with PCR. A LAMP assay was developed to detect C. sakazakii and it showed a higher sensitivity (9.1 fg/μL) compared to conventional PCR (9.1 pg/μL) and real‐time PCR (9.1 pg/μL) (Liu and others ). In another study, detection limit of developed LAMP assay for A. acidoterrestris was 4.5×10 −2 CFU per tube, while the detection limit of conventional PCR assay was 6.75×10 0 CFU per tube (Chen and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is one of the most popular targets for microbiological taxonomy (Chiu and others ). Sequences of the 16S‐23S rDNA ITS have been used as target template to design LAMP primers for detection of different bacteria in food systems, such as Alicyclobacillus acidoterrestris (Chen and others ) and Cronobacter sakazakii (Liu and others ). We validated that this currently developed LAMP assay can rapidly and precisely detect Y. pseudotuberculosis in commercial milk powder products.…”
Section: Introductionmentioning
confidence: 99%
“…[81] The proposed method by Zhang et al was based on propidium monoazide (PMA), loop-mediated isothermal amplification (LAMP), and nanozyme strip. LAMP is a gene amplification method for both live and dead cells, [82,83] whereas PMA is a DNA-binding dye that can penetrate dead or membrane-damaged bacteria, thereby inhibiting the subsequent amplification of DNA molecules in dead cells. [84] Thus, a combination of PMA and LAMP has been widely used to detect the bacterial viability.…”
Section: Metal Oxide-based Nanozymesmentioning
confidence: 99%